Contemporary South African Urbanization Dynamics - Todes, Alison et al (Urban Forum. Springer Science+Business Media B.V. 2010, 2010)
Abstract The paper provides an overview of urbanization patterns and trends in the current era in South Africa, focusing in particular on the key dynamics and driving forces underlying migration and urbanization. It considers overall demographic trends with regard to migration and urbanization, and points to some of the difficulties with data, and with the analysis of trends and patterns. The paper explores the changing rural context and dynamics, and some of the significant processes in this context: large-scale displacement of black people off farms, the impact of land reform, and conditions in the former homeland areas. Circular migration continues to be an important way in which households in rural areas survive, but some are unable to move, and are falling out of these networks. International migration—the consequence of both conditions in the home country and the draw of the South African economy— is another significant process fuelling mainly urban growth. The paper demonstrates the importance of cities in terms of economic growth and employment, and thus their attractiveness to migrants. Continuing migration to cities is of course a challenge for
Keywords: South africa and (urbanization patterns and trends)